From Pliny to Brexit: Spatial representation of the British Isles. Issue 4 (December 2016) - Hiatt, Alfred
Abstract This essay explores the representation of the British Isles on maps and related geographical texts over the course of the Middle Ages. Emphasizing the classical basis for representation of the islands, it examines articulations of insular identity in the debate over the date of Easter as presented in Bede'sEcclesiastical History, in Gerald of Wales'Topographia Hiberniae, and in later medieval maps of various genres, includingmappaemundi, regional maps, and portolan charts. It concludes with brief reflections on the contemporary crisis of insular identity manifest in the 2016 referendum on the United Kingdom's membership of the European Union.